A bibliometric analysis of Nuck canal cyst research - Muhammed Salih Süer; Gamze Kızıltan (International Journal of Abdominal Wall and Hernia Surgery)
BACKGROUND: Nuck canal cysts, or the hydrocele of the canal of Nuck, are rare conditions primarily affecting females. Over the past two decades, research interest in this area has increased, leading to a growing number of scientific publications. This bibliometric analysis aims to evaluate the trends in scientific publications related to Nuck canal cysts, identify leading contributors, and understand the global research landscape. MATERIALS AND METHODS: A comprehensive literature search on PubMed using the terms “Nuck canal cyst,” “canal of Nuck,” and “female hydrocele” was conducted. Limited to English-language articles and reviews published since 2000, the search concluded on July 5, 2024, yielded 166 relevant articles. After a review by two independent authors, 21 articles were deemed irrelevant, leaving 145 articles for further analysis. RESULTS: The annual scientific research production showed a significant increase in publications from 2011 onward, peaking around 2021. Leading institutions included Fujita Health University Okazaki Medical Center, Kurume University School of Medicine, and Sapporo Higashi Tokushukai Hospital. The USA, Japan, and Turkey emerged as the top contributing countries, with Japan leading in the number of overall publications. CONCLUSION: There has been a notable increase in research studies on Nuck canal cysts over the past decade, with significant contributions from specific institutions and countries. This growing body of research underscores the increasing interest and advancements in understanding, diagnosing, and treating Nuck canal cysts. Future research should continue to build on this foundation, exploring new diagnostic techniques, treatment options, and long-term patient outcomes.